Challenges, opportunities and innovations in social work field education - Egan, Ronnie; Hill, Nicole; Rollins, Wendy (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Social work field education is an integral component of social work education. This book collates and analyses the current research, debates, opportunities and practices in social work field education into one volume and contextualises this material within the broader context of social work. The sustainability of social work field education is gaining attention, with growing interest in challenges such as finding enough placements with accredited social workers, curriculum development, student diversity, student experience of placement and placement assessment of learning are also being examined by researchers and practitioners. This represents a challenge for the social work profession generally. Drawing on traditional and alternative pedagogical perspectives on field education and constructions of risk and uncertainty evident in current discourse, the book presents innovative responses to existing challenges and provides a reference point for future knowledge building in sustainable field education pedagogy and practice. Addressing the nature of the risks faced by universities in their provision of social work field education, as well as current research and practice learning innovation, this book will be of interest to university field education programs and industry field educators internationally"--
OCLC-licensed vendor bibliographic record.
Keywords: Social work education; Social service -- Fieldwork; Fieldwork (Educational method); SOCIAL SCIENCE / Social Work